Diadenosine Tetraphosphate (Ap4 A) Serves as a 5' RNA Cap in Mammalian Cells - František Potužník, Jiří; Nešuta, Ondřej; Škríba, Anton; Voleníková, Barbora; Mititelu, Maria-Bianca; Mancini, Flaminia; Serianni, Valentina; Fernandez, Henri; Spustová, Kristína; Trylčová, Jana; Vopalensky, Pavel; Cahová, Hana (Angewandte Chemie (International ed. in English), 2024)
The recent expansion of the field of RNA chemical modifications has changed our understanding of post-transcriptional gene regulation. Apart from internal nucleobase modifications, 7-methylguanosine was long thought to be the only eukaryotic RNA cap. However, the discovery of non-canonical RNA caps in eukaryotes revealed a new niche of previously undetected RNA chemical modifications. We are the first to report the existence of a new non-canonical RNA cap, diadenosine tetraphosphate (Ap4 A), in human and rat cell lines. Ap4 A is the most abundant dinucleoside polyphosphate in eukaryotic cells and can be incorporated into RNA by RNA polymerases as a non-canonical initiating nucleotide (NCIN). Using liquid chromatography-mass spectrometry (LC-MS), we show that the amount of capped Ap4 A-RNA is independent of the cellular concentration of Ap4 A. A decapping enzyme screen identifies two enzymes cleaving Ap4 A-RNA,NUDT2 and DXO, both of which also cleave other substrate RNAs in vitro. We further assess the translatability and immunogenicity of Ap4 A-RNA and show that although it is not translated, Ap4 A-RNA is recognized as self by the cell and does not elicit an immune response, making it a natural component of the transcriptome. Our findings open a previously unexplored area of eukaryotic RNA regulation.
Keywords: Diadenosine Tetraphosphate; Rats; dinukleosidfosfáty; fosfatasy; Ap4A; RNA Modification; Ap4A-RNA; Nudix Hydrolases; NUDIX hydrolasy; krysa rodu Rattus; RNA čepičky; zvířata; Humans; RNA Caps; Mammals; Phosphoric Monoester Hydrolases; savci; Dinucleoside Phosphates; RNA Cap; lidé; Animals